Benchmarking successful performances in elite Ladies Gaelic football. (2nd January 2022) - Kelly, Glen; McKenna, Odharnaith; Courtney, Sharon; Collins, Kieran; Bradley, Jonathan; Martin, Denise
ABSTRACT: The lack of sport science research conducted on female sport, makes it challenging for coaches and sport science practitioners to develop an evidence-based approach. Ladies Gaelic football (LGF) is the most popular female sport in Ireland with over 200, 000 members, however there has been no research to benchmark performance. The current study investigates the game characteristics of LGF by developing analysis system which could provide benchmark profiles of successful performance at elite level and evaluate the transferability of the game intelligence available within LGF's brother sport, Gaelic football (GF). Thirty-one games (62 performances) were analysed from the 2019 and 2020 TG4 All-Ireland Senior Ladies Football Championship using NacSport Scout+. Statistical differences between winning and losing performances were identified using paired sample t -tests (p ≤ 0.05) and Wilcoxon signed ranked tests (p ≤ 0.05). Winning teams were found to be significantly superior to losing teams, demonstrating superior ability to gain and use possession. LGF and men's GF teams adopt different strategic approaches to the game. The current study provides a first insight into the nature of LGF with benchmark data, facilitating a better understanding of the game demands of LGF and the key points of difference between male and LGF.